2015
DOI: 10.1515/jos-2015-0040
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Variations in the Effect of Interview Privacy and the Need for Social Conformity on Reporting Sensitive Information

Abstract: Privacy is an important feature of the interview interaction mainly due to its potential effect on reporting information, especially sensitive information. Here we examine the effect of thirdparty presence on reporting both sensitive and relatively neutral outcomes. We investigate whether the effect of third-party presence on reporting sensitive information is moderated by the respondent's need for social conformity and the respondent's country of residence. Three types of outcomes are investigated: behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…Several studies indicate that both the nature of topics being discussed and the role and/or relationship of the third party to the interviewee determine whether or not an interviewee adjusts their response. Topics that are sensitive and pose a potential threat to an interviewee appear to be more subject to the third-party effect (Barnett, 1998;Boeije, 2004;Diop et al, 2015;Milewski & Otto, 2017;Z. M. Mneimneh et al, 2015).…”
Section: What Is Known About Third-party Interview Effects?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate that both the nature of topics being discussed and the role and/or relationship of the third party to the interviewee determine whether or not an interviewee adjusts their response. Topics that are sensitive and pose a potential threat to an interviewee appear to be more subject to the third-party effect (Barnett, 1998;Boeije, 2004;Diop et al, 2015;Milewski & Otto, 2017;Z. M. Mneimneh et al, 2015).…”
Section: What Is Known About Third-party Interview Effects?mentioning
confidence: 99%
“…Methodological research has thus sought to systematically understand when and how the presence of a third party may affect the scope, the validity, or the reliability of interview data. This research has found that the extent of a third-party's influence is largely determined by two factors: (a) the sensitivity of the questions being asked (Barnett, 1998;Boeije, 2004;Diop et al, 2015;Mneimneh et al, 2015), and (b) the power differentials between parties involved (Cronk et al 2009;Taietz, 1962;Tourangeau & Yan, 2007;Zipp & Toth, 2002). To date, however, no research has examined the potential effect of a thirdparty scientific expert.…”
Section: Introductionmentioning
confidence: 99%
“…third parties during the interview (Diop, Le, and Traugott 2015;Mneimneh et al 2015). However, theories of survey-taking behavior (for example, Hox, de Leeuw and Vorst 1995;Loosveldt and Storms 2008) suggest a more pervasive possibility: that political conditions in the Arab world may instill negative perceptions of the entire survey research enterprisewhatever the characteristics of an individual surveyand these general attitudes toward surveys may influence participation and response behavior in ways that produce misleading results.…”
mentioning
confidence: 99%
“…Indeed, the MENA setting is known to pose particular challenges for survey research, due largely to conservative cultural norms and pervasive authoritarianism (Benstead 2018), and scholars have given special attention to how these and other contextual factors may introduce bias in Arab opinion surveys. For instance, previous research has examined the effects of systematic nonresponse when Arab respondents distrust a survey sponsor (Corstange 2014(Corstange , 2016Gengler et al 2019); refusal to answer survey questions due to doubts about survey confidentiality (Benstead 2018); and measurement error on sensitive items due to a lack of survey privacy during the interview (Diop et al 2015;Mneimneh et al 2015).…”
mentioning
confidence: 99%